Agenda for meeting on 1 June 1938
043-0071-001 SPANISH MEDICAL AID COMMITTEE. A Committee meeting will be held at 24, New Oxford St. W.C.1. on Wednesday next, June 1st. at 8.45.p.m. AGENDA. 1. Minutes of meeting of May 25th. 2. Matters arising therefrom. 3. Special Correspondence. 4. Report of Special Financial Sub-Committee. 5. Report of Personnel and Technical Sub-Committee. 6. Any other business. 292/946/43/71